A method for high heat flux fatigue test of W/Cu/steel small mock-up using normal cooling conditions. (September 2021) - Wang, Ji-Chao; Wang, Wanjing; Li, Qiang; Qin, Sigui; Lei, Mingzhun; Luo, Guang-Nan
Highlights: Amethodfor HHF test of W/steel small mockup is introduced, using normal coolant conditions. Fatigue life of W/Cu/steel mockup is preliminary predicted and tested. The experiment result shows consistency with the predicted life. Abstract: Fatigue property of W/steel joints is important for predicting the life of First Wall (FW). Few facilities can satisfy the harsh coolant parameters of FW. It is necessary to develop a method to evaluate the fatigue property, using coolant with normal pressure and temperature, for example 0.2 MPa and 25 ℃. Combining numerical calculation and experiment validation. Building the relationship between different heat flux and the maximum temperature and strain, predicting the life of FW according to Manson-Coffin formula (MC). Verifying by the fatigue test in a High Heat Flux test platform equipped with an electron gun, the experimental results have shown the feasibility of this method.